Kinetic Model of Urea Desorption from a Starch-Based Controlled Release Fertilizer - Herry Santoso (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2015)
The use of fertilizer has increased as the agriculture become more intensified. This increment caused a lot of environmental issue, such as water and soil pollution. It is well-known that conventional fertilizer does not have a good efficiency in practice due to fertilizer leaching or washing off problem. This problem can now be significantly minimized by using a controlled release system. There are a lot of models that have been used to study controlled release drugs, but only a few are used to describe controlled release fertilizers. In this study, we propose a simple model to represent urea desorption from a starch-based controlled release fertilizer and then use the model to predict the urea desorption characteristics of the fertilizer. The controlled release fertilizer was made from starch-based hydrogel loaded with urea. The urea desorption from the starch-based controlled release fertilizer in the water is then tested. The kinetic data collected from the urea desorption experiment is used to derive, verify, and validate the kinetic model of urea desorption from the starch-based controlled release fertilizer.